Skill and performance to formulate evidence-based practice among nursing students: A qualitative study - Carissa Muthia Putri Nugroho; Titis Kurniawan; Hasniatisari Harun; Nursiswati Nursiswati; Eka Afrima Sari (Malahayati International Journal of Nursing and Health Science, 2024)
Background: The PICO framework is frequently applied to formulate question for conducting literature searching in the evidence-based practices (EBPs) development. However, students experienced challenges in fitting the clinical questions into PICO's format. In Indonesia, the EBP was mostly taught conventionally through lectures and discussions. There was no specific evaluation for assessing the accuracy of the PICO formula. Previous studies indicated that incorporating visual art in learning effectively improves students' observation skills, self-confidence, communication skills, and promotes transformational learning.Purpose: To describe the implementation of the PICO game and visual art as an EBP learning method and evaluate the accuracy of the PICO formula and the visual art created by nursing students, including their perspectives on the applied EBP learning method.Method: This descriptive study was conducted at a secondary hospital in Sumedang District, West Java-Indonesia, in July 2023. Totally 53 nursing profession program (NPP) students of a University in Indonesia were voluntarily recruited as participants. They divided into 9 groups and received a description of how to play the PICO game and visual art for developing the PICO formula question. Each group required to develop PICO questions from the PICO trigger pictures and keywords on the PICO worksheets and to draw at least one visual art illustration from the developed PICO question. At the end of those sessions, they were also required to provide opinions on this EBP learning approach. The PICO question accuracy was assessed using the PICO formula observation sheet, while the visual art compatibility was measured using the visual art observation sheet. Quantitative data were analyzed descriptively and the students’ perspectives on the EBP learning processes were analyzed by identifying the topic mostly described.Results: There were 63 PICO formulas and 18 visual art illustrations. Most of the PICO formulas (93.7%) were identified as accurate. However, more than one-third (41.3%) of the PICO formula did not include the C (comparison) component. More than half of the developed visual art illustrations (61%) were inappropriately describing the developed PICO formula. Participants reported that using PICO Games and visual art was an interesting and fun approach that enhanced their comprehension of the PICO question formula, EBP, and improved their teamwork capacity.Conclusion: The PICO game and visual art learning method facilitates high accuracy of the PICO question formula and is perceived as an effective and interesting EBP learning method. However, as the “C” (comparison) is the PICO component mostly found uncompleted, it is important to elaborate more on this issue in the EBP learning session. It is also important to extend the duration of the EBP learning method to facilitate students drawing the expected visual art appropriately. Further studies are needed to further confirm and follow up on the findings of this study.